Finding Volunesia: An Exploration of How Volunteer Identity and Volunteer Learning Through the Life Course Transforms Participants and Develops Enduring Leaders. - GARLAND, SHELLI ANN (Trinity College Dublin. School of Education. Discipline of Education, 2020)
Ireland has a rich history in volunteering. A culture of neighbor helping neighbor, and giving one's time, energy and commitment to others outside of one?s immediate family. The purpose of the research is to examine life course influences on volunteer identity and learning through volunteering toward a contribution to lifelong learning. This research seeks to understand the learning experiences of Active Volunteers (AVs) within the context of wider society and changing social structures. It closely examines the concept of identity and learning through the life course, and why it is considered an issue of critical importance in the context of community engagement and volunteer longevity. This research explores the lived-experiences of the AV in Ireland post-tertiary education, and interpretation of the relationship between informal learning and identity through socially defined influences and experiences of family, environment, customs and lifestyle, to gain insight and understanding of volunteer identity and learning as informal learning over the life course. Through an inductive approach that adopts social identity theory and lifelong learning theory, this research is underpinned by a constructivist interpretive paradigm. Such an approach is qualitative, holistic, and aims to understand and explain the personal ways individuals relate volunteering with their identity, learning as part of their volunteer experience, and understanding identity through learning. Through in-depth interviews, reflective journaling, and identity workshops, my research investigated participant perceptions of learning through volunteering. I looked at identity from the view point of the AV and their understanding of what learning means, 'if' or 'how' those understandings change over time; and to provide a deeper understanding of the concept of learning that remains. The research findings found four distinct Active Volunteer Dispositions (AVDs) as volunteer leader types that, when properly cultivated, can transform and revolutionize how we understand volunteer identity and learning. Personal and social identity is important for individual learning, and further study into the interconnected relationship between identity and informal learning over the life course can be useful for creating, supporting, and maintaining important volunteer leader learning models. Adult and higher education, as institutions of society, have a fundamental role to play in promoting the ideals of democracy, social justice, and human rights and contributing to the social development of society. The findings are discussed in terms of typing the AVDs and recommendations in terms of supports for AVs; ideas for learning and community-based program development in adult education; and suggestions for national and international educational policy development for the betterment of wider civic society.
APPROVED
Keywords: Volunteer learning and leadership; Volunteer identity; Life course theory; Formal and informal learning; Adult and life long learning